2017
DOI: 10.1002/hipo.22693
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal imaging reveals subhippocampal dynamics in glutamate levels associated with histopathologic events in a mouse model of tauopathy and healthy mice

Abstract: Tauopathies are neurodegenerative disorders characterized by abnormal intracellular aggregates of tau protein, and include Alzheimer’s disease, corticobasal degeneration, frontotemporal dementia, and traumatic brain injury. Glutamate metabolism is altered in neurodegenerative disorders manifesting in higher or lower concentrations of glutamate, its transporters or receptors. Previously, glutamate chemical exchange saturation transfer (GluCEST) magnetic resonance imaging (MRI) demonstrated that glutamate levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 90 publications
3
60
0
Order By: Relevance
“…An advantage of this imaging method is that the glutamate measurements are devoid of any glutamine contamination. The GluCEST technique has been implemented in studies of mouse models of Alzheimer's disease, which demonstrated the sensitivity of the method to detect decreased concentrations of glutamate in diseased mice compared with healthy, age‐matched controls . In the mouse model of Parkinson's disease, increased GluCEST was measured from the striatum compared with the healthy controls .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An advantage of this imaging method is that the glutamate measurements are devoid of any glutamine contamination. The GluCEST technique has been implemented in studies of mouse models of Alzheimer's disease, which demonstrated the sensitivity of the method to detect decreased concentrations of glutamate in diseased mice compared with healthy, age‐matched controls . In the mouse model of Parkinson's disease, increased GluCEST was measured from the striatum compared with the healthy controls .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 For example, elevated glutamate likely contributes to "excitotoxic" neuronal cell loss in Alzheimer's disease through overstimulation of glutamatergic receptors. [6][7][8][9] Decreased glutamate is observed in animal model of Alzheimer's disease and in patients with advanced pathology, [10][11][12][13] particularly within the hippocampus, and is positively correlated with the progressive loss of glutamate transporter proteins in brain regions associated with memory and cognitive function. 14,15 Although altered glutamate levels are implicated in the pathogenesis of neurological and neuropsychiatric diseases, glutamate has also been shown to decrease with age in the neurotypical brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, although these observations suggest a role of Tau in the nuclear compartment, this field is still largely unexplored and it is not known whether nuclear Tau could have a role in modulating gene expression or some aspects of chromatin function that might be relevant for the pathophysiology of tauopathies. Here, we provide the first demonstration that the nuclear pool of Tau modulates the expression of the vesicular glutamate transporter VGluT1, which is known to be strongly upregulated in early phases of tauopathies [25,26]. Moreover, we show that increasing the soluble pool of Tau favours its nuclear translocation and increases the expression of VGluT1.…”
Section: Introductionmentioning
confidence: 59%
“…To investigate whether nuclear Tau might have a role in modulating gene expression, we checked the expression of disease-related genes in Tau-overexpressing cells. A growing body of evidence suggests that glutamate release is altered during the progression of tauopathies, causing an early synaptic hyperexcitability in the asymptomatic phase mediated by Tau [11,25,26].…”
Section: Tau Is Detectable In the Soluble And Chromatin-bound Nuclearmentioning
confidence: 99%